Late Quaternary glacier and sea-ice history of northern Wijdefjorden, Svalbard - Allaart, Lis; Müller, Juliane; Schomacker, Anders; Rydningen, Tom Arne; Håkansson, Lena; Kjellman, Sofia Elisabeth; Mollenhauer, Gesine; Forwick, Matthias (Boreas, 2020)
The deglaciation history and Holocene environmental evolution of northern Wijdefjorden, Svalbard, are reconstructed using sediment cores and acoustic data (multibeam swath bathymetry and sub‐bottom profiler data). Results reveal that the fjord mouth was deglaciated prior to 14.5±0.3 cal. ka BP and deglaciation occurred stepwise. Biomarker analyses show rapid variations in water temperature and sea ice cover during the deglaciation, and cold conditions during the Younger Dryas, followed by minimum sea ice cover throughout the Early Holocene, until c . 7 cal. ka BP . Most of the glaciers in Wijdefjorden had retreated onto land by c . 7.6±0.2 cal. ka BP . Subsequently, the sea‐ice extent increased and remained high throughout the last part of the Holocene. We interpret a high Late Holocene sediment accumulation rate in the northernmost core to reflect increased sediment flux to the site from the outlet of the adjacent lake Femmilsjøen, related to glacier growth in the Femmilsjøen catchment area. Furthermore, increased sea ice cover, lower water temperatures and the re‐occurrence of ice‐rafted debris indicate increased local glacier activity and overall cooler conditions in Wijdefjorden after c . 0.5 cal. ka BP . We summarize our findings in a conceptual model for the depositional environment in northern Wijdefjorden from the Late Weichselian until present.